Cooperation patterns in smallcell networks: Risks and opportunities to distinguish the win-win model - Amirhossein Ghanbari; Jan Markendahl; Ashraf Awadelakrim Widaa (International Telecommunications Society (ITS), 2013)
Cooperation and collaboration with either competitors and/or other actors in the ecosystem seems to become a relevant method for Mobile Network Operators (MNOs) in order to decrease costs and boost revenues at the same time. But, there are always risks and imperfections in front of such models such as losing control over network, empowering existing or potential competitors and unwillingness to contribute evenly in different cases with other actors. In this paper we discuss possible cooperation patterns for indoor smallcell networks, adopted from successful cooperation patterns in macro cellular networks. This is done by analyzing three main areas: Deployment of smallcells, sharing strategies and outsourcing. Based on the works done in this field, an intersection of these three areas is missing that is studying possible cooperation patterns with all possible actors (operators, third parties and Facility owners) of shared smallcell networks. The aim of this paper is to see how it is possible to enable cases where all involved actors benefit from the cooperation pattern, by looking into existing solutions as well as proposing new patterns that a multitude of actors may be willing to adopt. Since there is no distinct answer for such a question, the proposed Wholesale model or Comprehensive system helps mobile operators to rethink about smallcell specific business models. This investigation enables distinguishing between revenue-efficient and cost-efficient smallcell network deployments for both operators and other investors.
Keywords: 330